In vitro and in silico study of Aloe vera leaf extract against human breast cancer. Issue 16 (17th August 2020) - Majumder, Ranabir; Parida, Pratap; Paul, Samrat; Basak, Piyali
Abstract: Aloe vera leaf contains some bioactive compounds that have a strong binding affinity toward estrogen receptor as compared to standard drug tamoxifen. In this study, we have found that the IC50 of Aloe vera leaf extract against breast cancer cell line (MCF-7) is 23 µg/mL which is much lower than the IC50 (332 µg/mL) of Aloe vera leaf extract against non-cancerous cell line (NIH-3T3). We have also calculated the total concentration of phenolic acid (385.662 µg/mL), flavonoids (160.402 µg/mL) and alkaloids (276.754 µg/mL) in Aloe vera leaf extract. The free radical scavenging activity of Aloe vera leaf extract is 67% to 89% (at 50 to 300 µg/ml). Our virtual molecular docking study suggests that bioactive compounds like Aloe-emodin (−8.8 Kcal/mol), 7-hydroxy-2, 5 dimethylchromone (−7.5 Kcal/mol), Beta-sitosterol (−7.3 Kcal/mol) etc. have a greater binding affinity toward estrogen alpha receptor as compared to standard drug Tamoxifen (−6.4 Kcal/mol).